Cost-effectiveness analysis of Toripalimab regimen for extensive-stage small-cell lung cancer in China and America - Yang, Jing; Chen, Fang; Li, Junlin; Zhou, Yujie; Wang, Hao; Long, Yunchun (Frontiers in Immunology, 2025)
ObjectivesToripalimab combined with chemotherapy is a clinically valuable and important regimen in the treatment of extensive−stage small−cell lung cancer (ES-SCLC). However, there are no studies on the cost-effectiveness of this regimen, so this study was designed to evaluate the cost-effectiveness of Toripalimab regimen for the treatment of ES-SCLC from the perspectives of the Chinese health system and the U.S. health system, respectively.MethodsA partitioned survival model was developed to simulate the clinical progression and cost consumption of ES-SCLC using the results of the EXTENTORCH study as a source of survival data and incorporating direct medical costs. Model output metrics included incremental cost-effectiveness ratio (ICER), quality-adjusted life-years (QALYs), incremental QALYs, total costs, and incremental costs. The cost-effectiveness of the Toripalimab scheme was judged by comparing the ICER with the willingness to pay (WTP). The robustness of the model was verified by sensitivity analysis and scenario analysis.ResultsThe results of the basic analysis showed that from the perspective of the Chinese health system, the Toripalimab group gained 0.18 QALYs more at a cost of 5,204, with an ICER of 29,139/QALY (<WTP). From the standpoint of the U.S. health system, the Toripalimab group spent 156,923 more and also gained 0.17 QALYs more, but the ICER (915,965/QALY) was much higher than the WTP. Sensitivity and scenario analyses showed the model to be generally stable.ConclusionsCompared with chemotherapy, the Toripalimab regimen for the treatment of ES-SCLC is cost-effective from the perspective of the Chinese health system, but not from the perspective of the US health system.